MENGGUGAH IDENTITAS KEBANGSAAN MELALUI PUISI - Besse Darmawati (JENTERA: Jurnal Kajian Sastra, 2017)
A good literary works are able to give positive values to human being. This research aims to describe the elements, meaning, and cultural values in the poems that contain positive values for human life. The researcher applies qualitative method through objective and intuitive approaches. The meaning and cultural values of the poems are intuitively gained from the result of the analysis objectively. The data are “Kata Cinta Usia 51”, “Jabatan Yang Hilang” and “Kita Adalah Pemilik Sah Republik Ini.” Objectively, these poems have the themes of belief in worldly life, the excessive mistaken, and the resurrection of life. Intuitively, the meaning of these three poems makes people aware that life is only temporary, so they cannot escape from gratitude, must not feel despair in facing hardships, are not mistaken by the beauty of the world, and strive to achieve a good quality of life. The cultural values of these poems are gratitude, fortitude, faithful, patience, bravery, firmness, and responsibility. These reflect the characters and identities of young generations as their identities, so they are different from other nations, in order to awaken their identity as a dignified Indonesian nation.   ABSTRAKKarya sastra yang baik mampu memberi nilai positif terhadap manusia. Penelitian ini bertujuan untuk mendeskripsikan unsur, makna, dan nilai budaya dalam puisi yang bernilai positif bagi kehidupan manusia. Penulis menerapkan metode penelitian deskriptif kualitatif melalui pendekatan objektif dan intuitif. Makna dan nilai budaya dalam puisi secara intuitif diperoleh dari hasil analisis secara objektif. Data adalah puisi “Kata Cinta Usia 51,” “Jabatan Yang Hilang,” dan “Kita Adalah Pemilik Sah Republik Ini.” Secara objektif, puisi tersebut bertemakan keyakinan terhadap kehidupan duniawi, kekeliruan yang berlebihan, dan kebangkitan hidup. Secara intuitif, makna ketiga puisi tersebut menyadarkan manusia bahwa hidup hanya sementara sehingga tidak terlepas dari rasa syukur, jangan putus asa menghadapi cobaan, jangan keliru dengan keindahan dunia, dan berjuang mencapai kehidupan yang berkualitas. Adapun nilai budaya dari puisi tersebut adalah kesyukuran, ketabahan, keyakinan, kesabaran, keberanian, keteguhan, dan bertanggung jawab. Hal demikian mencerminkan karakter dan identitas anak bangsa sebagai jati diri mereka, sehingga berbeda dengan bangsa lain, dalam rangka menggungah identitas sebagai bangsa Indonesia yang bermartabat.